The Influence of Taste and Price on Purchase Interest in Bebek Madu 88 Bekasi - Anggi Achmad Akbar; Hadita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to find out whether taste (X1) and affordable price (X2) have an influence on consumer or buyer interest (Y) in Bebek Madu 88 Bekasi. The data collection technique used in the research was a survey using gform, with the population being all consumers who came, and the sample obtained was 30 people. From the results of data processing, there are results obtained from simple regression analysis that there is an influence of taste and price on buyer interest of 72%, while the remaining 28% is influenced by other variables. This research aims to find out whether taste and affordable price have an influence on consumer or buyer interest in Bebek Madu 88, and the results obtained are that the calculated t value for taste is 2.938 and the t table value is 2.048, so it can be interpreted that there is an influence between taste to buyer interest